Mitigating the influence of analysts who issue aggressive stock price targets: the role of joint versus separate evaluation - Chee, Vincent (2022)
Investors frequently rely on individual analysts’ stock price targets. Aggressive price targets often reflect analysts’ attempts to strategically influence investors. Therefore, investors’ welfare may be compromised if they take aggressive price targets at face value. In this study we examine conditions under which investors are more likely to infer that analysts who issue aggressive price targets are acting strategically. Investors can evaluate multiple analysts’ price targets with or without other related information (e.g., earnings estimates). Investors can also evaluate the information provided by multiple analysts jointly or separately. Two experiments find that as predicted, when investors evaluate multiple analysts’ price targets without earnings estimates, there is no difference in investors’ perceptions about whether the aggressive analyst is acting strategically across joint versus separate evaluation. However, also as predicted, when investors evaluate multiple analysts’ price targets along with their earnings estimates, investors perceive the aggressive analyst as acting more strategically under joint evaluation than under separate evaluation. Our findings suggest that when investors evaluate multiple analysts’ price targets with other related information such as earnings estimates, adopting joint evaluation can reduce the likelihood that investors are overly influenced by aggressive analysts.